2012
DOI: 10.1159/000334684
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Eradication Improves Gastric Atrophy and Intestinal Metaplasia in Long-Term Observation

Abstract: Background and Aim:Helicobacter pylori has been shown to cause atrophic gastritis and intestinal metaplasia (IM), both of which are precancerous lesions. To clarify the mechanism by which H. pylori eradication prevents gastric cancer, we monitored atrophy and IM improvement in gastric mucosa over a long period after H. pylori eradication. Methods: We monitored 118 patients (72 males, 46 females; mean age 61.3 ± 5.1 years) for a mean of 8.6 years (range 5–13) after successful H. pylori eradication. Biopsy speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 49 publications
1
42
0
2
Order By: Relevance
“…The subjects of their study were a patient population who had moderate-to-severe atrophic mucosa accompanied by intestinal metaplasia, indicating that H. pylori eradication is effective even in patients who have advanced atrophy of the gastric mucosa. Based on long-term observation after H. pylori eradication, it has also been reported that eradicating this microorganism results in marked improvement of gastric mucosal atrophy and intestinal metaplasia, which are changes strongly related to the development of gastric cancer [25]. Therefore, it can reasonably be inferred that H. pylori eradication in cases with open-type atrophy is essential for preventing the occurrence of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The subjects of their study were a patient population who had moderate-to-severe atrophic mucosa accompanied by intestinal metaplasia, indicating that H. pylori eradication is effective even in patients who have advanced atrophy of the gastric mucosa. Based on long-term observation after H. pylori eradication, it has also been reported that eradicating this microorganism results in marked improvement of gastric mucosal atrophy and intestinal metaplasia, which are changes strongly related to the development of gastric cancer [25]. Therefore, it can reasonably be inferred that H. pylori eradication in cases with open-type atrophy is essential for preventing the occurrence of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[51][52][53][54][55] Conversely, H pylori eradication in patients with autoimmune atrophic gastritis is followed by improved gastric acid and ascorbate secretion in many, and partial or complete remission of atrophic gastritis in a variable proportion of patients. [56][57][58][59][60] In our experience, H pylori eradication is followed by a significant decrease in serum gastrin levels in almost all patients, but complete remission accompanied by disappearance of circulating antiparietal cell antibodies (APCAs) is only observed in a limited number of patients. Failure to achieve complete remission by H pylori eradication in the majority of patients does not necessarily argue against the role of H pylori in the pathogenesis of autoimmune gastritis but more likely indicates that a point of no return may be reached beyond which the autoimmune process may no longer require the continued presence of the inducing pathogen.…”
Section: Relation Between Autoimmune Gastritis and H Pylori Infectionmentioning
confidence: 94%
“…In autoimmune gastritis patients with coexistent active H pylori infection, H pylori eradication may be useful for arresting the progress of disease and improving response to oral iron. [56][57][58][59][60] Patients with celiac disease should be started on a gluten-free diet with regular follow-up to ensure response and compliance. 67 …”
Section: Specific Treatmentmentioning
confidence: 99%
“…This can be explained by the smaller number of gastric glands in the normal antral mucosa (18,152) . The results of H pylori eradication on atrophic gastritis are often controversial (38,102,111,203) . A recent meta-analysis study involving 12 trials analyzing 2,648 patients with atrophic gastritis of the antrum found no significant reversibility of atrophic changes in the antrum following H pylori eradication (203) .…”
Section: Statement 15mentioning
confidence: 99%